2003
DOI: 10.1902/jop.2003.74.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Constitutionally Hyperreactive Neutrophils in Periodontitis

Abstract: Our findings suggest that the increased CL from peripheral neutrophils in periodontitis may be related to a constitutionally greater responsiveness of the Fcgamma-receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 28 publications
8
104
2
1
Order By: Relevance
“…In the present study, we found a significant rise in the level of LPO in Group 1 and Group 2 in comparison with healthy controls (Group 4). This result is in agreement with other studies [8,42,45]. In the study by Tsai et al [8], increased concentration of LPO was found in GCF and whole saliva.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we found a significant rise in the level of LPO in Group 1 and Group 2 in comparison with healthy controls (Group 4). This result is in agreement with other studies [8,42,45]. In the study by Tsai et al [8], increased concentration of LPO was found in GCF and whole saliva.…”
Section: Discussionsupporting
confidence: 93%
“…An increased LPO level following periodontitis has been noted in many studies [6,8,42]. In addition to oxygen-derived free radicals, glycated collagen has also been shown to raise the oxidative breakdown of lipids compared to normal collagen which causes increased MDA in serum and tissues of diabetic subjects [24].…”
Section: Discussionmentioning
confidence: 95%
“…By using microarrays not tailored for the disease we were able to elucidate transcriptional changes that were previously not part of current understanding. These studies have identified several functional groups of genes up-regulated in periodontitis patients' neutrophils compared with healthy controls, providing a better understanding of the molecular processes underpinning this highly prevalent disease in which peripheral neutrophils generate increased levels of ROS in the presence and absence of stimulation (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…The resultant collateral host tissue damage to the supporting periodontal tissues leads to progressive periodontitis and ultimately culminates in tooth loss (6). Several studies have demonstrated that PBN from chronic periodontitis patients are not only hyperreactive, in response to Fc␥R stimulation by periodontal pathogens, but also hyperactive, with respect to baseline unstimulated ROS production (7)(8)(9)(10). Although a host molecular defect in intracellular lipid signaling may explain peripheral neutrophil ROS hyperreactivity in the relatively rare form of the disease, localized aggressive periodontitis (11), this mechanism does not explain the patient predisposition observed in chronic periodontitis.…”
Section: P Eripheral Blood Neutrophils (Pbn)mentioning
confidence: 99%
See 1 more Smart Citation